2001
DOI: 10.2172/789186
|View full text |Cite
|
Sign up to set email alerts
|

Summary report on Phase 1 feasibility study of in-drift diffusion

Abstract: This report summarizes the work performed and findings obtained during the Phase 1 (feasibility study) of the Engineered Barrier System (EBS) in-drift diffusion evaluation. The objective of this work is to characterize and reduce uncertainties associated with measurements of diffusion coefficients and modeling of diffusion processes. Phase 1 of the study evaluates measurement and modeling uncertainties as well as scoping alternative measurement and modeling approaches.Phase 2 of the study consists of rigorous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, diffusivity measurements are not the best tool for determining whether a specific medium is at criticality. One better option would be to vacuum‐saturate the sample with a tracer, then examine the tracer profile using a high‐resolution method such as laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS; Hu et al [2001]). This will give an edge‐accessible porosity profile which can then be compared with theoretical predictions for different connectivities [ Ewing and Horton , 2002].…”
Section: Implications and Applicationsmentioning
confidence: 99%
“…However, diffusivity measurements are not the best tool for determining whether a specific medium is at criticality. One better option would be to vacuum‐saturate the sample with a tracer, then examine the tracer profile using a high‐resolution method such as laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS; Hu et al [2001]). This will give an edge‐accessible porosity profile which can then be compared with theoretical predictions for different connectivities [ Ewing and Horton , 2002].…”
Section: Implications and Applicationsmentioning
confidence: 99%
“…The interior surface was then mapped by adjusting the laser focus at each sampling location for the exposed rough surface. Stable responses were obtained during testing of these tuff elements despite the rough surface (Hu et al, 2001). A series of CT images are shown in Figure 5a for partially saturated 6.3−9.5 mm gravel.…”
Section: Diffusion Measurements By the Micro-scale Mapping Methodsmentioning
confidence: 95%
“…CRWMS M&O (2000b) reported that this diffusion data set was well correlated in terms of a power-dependence (Archie's law type) on the volumetric water content, and used a resultant "universal" power function to represent diffusive transport of radionuclides through the invert. However, in waste emplacement drifts, characterized by a humid environment with or without the presence of liquid water, crushed porous rock may provide unique characteristics that vary greatly from this generic power function (Wang et al, 2001;Hu and Wang, 2003). For example, Conca (1990) placed four different size fractions of tuff gravel samples (2-4 mm, 4-6.3 mm, 6.3-9.5 mm, and 15-25.4 mm) for equilibrium inside a chamber with a nearly 100% humidity atmosphere.…”
mentioning
confidence: 99%
“…Measurements along the outside surface of the sink cube indicated that a nonsorbing tracer (ReO 4 − ) diffused along the surface at a rate similar to its aqueous diffusion rate in bulk water (Hu et al 2001 . This is a factor of 10 5 larger than the measurement.…”
Section: Modification For Porosity and Saturationmentioning
confidence: 99%